2021
DOI: 10.1038/s41598-020-80605-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal saliva omics responses to immune perturbation: a case study

Abstract: Saliva omics has immense potential for non-invasive diagnostics, including monitoring very young or elderly populations, or individuals in remote locations. In this study, multiple saliva omics from an individual were monitored over three periods (100 timepoints) involving: (1) hourly sampling over 24 h without intervention, (2) hourly sampling over 24 h including immune system activation using the standard 23-valent pneumococcal polysaccharide vaccine, (3) daily sampling for 33 days profiling the post-vaccina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 87 publications
4
26
0
Order By: Relevance
“…Interferon signaling is crucial in antiviral defense, cell regulation and growth, and immune response modulation [50]. Our Reactome pathway analysis results are consistent with the results of our saliva multi-omics study [15], which observed that vaccination activates various immune response and regulation pathways, which are also identified in our present results, including ER-Phagosome pathway, Interferon alpha/beta and gamma signaling, cytokine signaling, and MHC antigen presentation.…”
Section: Ppsv23 Pathway Activations Following Perturbation In Salivasupporting
confidence: 92%
See 4 more Smart Citations
“…Interferon signaling is crucial in antiviral defense, cell regulation and growth, and immune response modulation [50]. Our Reactome pathway analysis results are consistent with the results of our saliva multi-omics study [15], which observed that vaccination activates various immune response and regulation pathways, which are also identified in our present results, including ER-Phagosome pathway, Interferon alpha/beta and gamma signaling, cytokine signaling, and MHC antigen presentation.…”
Section: Ppsv23 Pathway Activations Following Perturbation In Salivasupporting
confidence: 92%
“…Our RNA-seq time series raw data were retrieved from the Gene Expression Omnibus database under accessions GSE108664 and GSE100441 for the saliva and B cell experiments, respectively. The study of the immune response to the PPSV23 vaccine in saliva probed the expression of a potential 84647 gene identifiers (GENCODE annotation [36]) at 24 time points [15]. The other study of drug activation by Rituximab in B cells provided a dataset for 6 time points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations